Shared-decision-making Behavior in Hospitalized Patients: Investigating the Impact of Patient's Trust in Physicians, Emotional Support, Informational Support, and Tendency to Excuse Using a Structural Equation Modeling Approach - Zahra Chegini PhD; Sheikh Mohammed Shariful Islam PhD (Journal of Patient Experience, 2021)
Patient participation in care decisions is facilitated by shared-decision-making (SDM). This study, therefore, aims to explore the impact of patient's trust in physicians, emotional support, informational support, and tendency to excuse on SDM. A cross-sectional study was conducted at the medical–surgical wards of 6 similar-sized public hospitals in Tabriz, northwest Iran, using a self-administered questionnaire, with 321 cases collected from October to December 2019. The structural equation modeling (SEM) analysis was used to test the hypothetical model. Using the SEM approach, the findings fully confirmed the study hypothesis, and patients’ trust in physician (Beta = −0.44), emotional support (Beta = 0.29), tendency to excuse (Beta = 0.18), and informational support (Beta = 0.58) predicted the inpatient's SDM behavior ( R 2  = 0.65, goodness-of-fit index = 0.902). To improve patient outcomes, physicians might advise incorporating techniques such as improving patient trust, informational and emotional supports to improve SDM. Improving the psychosocial skills of physicians also seems to be essential to help patients express their concerns.